Participatory natural resource management for sustainable agriculture (University of the Phillipines Diliman, 2004)
Sustainable Agriculture and Natural Resource Management activities seek to increase agricultural productivity through adoption of practices that maintain the long term ecological and biological integrity of natural resources. Activities in this sub-sector cut across the rural, social, and environmental issues of natural resource management to sustain significant increases in farm productivity through the efficient use of land and other resources. The goal is to provide better economic returns to individuals and contribute to the quality of life and economic development.